Precarious employment in Peru, 1980-2008: an alternative explanation of the problem and public policy proposals for overcoming it - Gamero Requena, Julio (2010)
The precariousness of employment deepened in the context of the structural adjustment of the 1990s, inducing a relative disqualification of the labor force to the detriment of the bargaining power of the working sector; overcoming these results requires a convergent approach between economic, social and labor policies. In short, we need a scheme that incorporates equity in labor relations without undermining the achievement of greater productivity and competitiveness of the economy.